The Use of Structural Intersectionality as a Method to Analyze How the Domestic Violence Civil Protective Order Process Replicates Inequality - Durfee, Alesha (Violence against women, 2021)
While protective orders remain a commonly used resource, multiply marginalized survivors are often unable to file for, obtain, serve, and enforce orders. I argue that using structural intersectionality as a method is the best way to reveal how the protective order process replicates broader social inequalities. I advocate for an alternative way of using structural intersectionality. I first identify the mechanisms by which inequalities exist and then describe how these can be traced back to intersecting social identities. In doing so, I highlight the importance of historical context and the blurring of the civil and criminal legal systems.